96 years after the death of Joaquín Capelo. An approach to his public career - Laya Alcedo, Ana Esther (2024)
Joaquín Capelo truly left a significant mark on the history of Peru between 1871 and 1919. His versatility as an engineer, intellectual, and social activist made him a reference in a period of great change. His positivist and nationalist approach not only guided his work, but also reflected the aspirations of a society that sought to modernize and advance in various areas. His dedication to education and sociology is admirable, and his participation in teaching and publishing relevant works helped train new generations. Furthermore, his connection with the Amazon and his interest in governability and the nationalization of the territory are aspects that highlight his comprehensive vision of the country’s development. His commitment to the popular classes and his defense of indigenous communities is especially notable, demonstrating a social sensitivity that is fundamental in any leader. Although his legacy is complex and has been the subject of controversy, it is essential to revalue it in Peruvian historiography, since its influence on the intellectual, political and social modernization of the country is undeniable.